Murine typhus and other potentially lethal rickettsial diseases in Chiapas, Mexico - Jorge Castañeda-Gómez; Óscar Delgado-Cuéllar; Luis Tinoco-Gracia; Rogelio Danis-Lozano (Instituto Nacional de Salud Pública, 2023)
Not available